Water properties in food, health, pharmaceutical and biological systems : ISOPOW 10 - Reid, David; Sajjaanantakul, Tanaboon (Wiley-Blackwell, 2010)
Focuses on the comprehension of the properties of water in foods, enriched by the approaches from polymer and materials sciences, and by the advances of analytical techniques. This book covers the topics presented at the 10th The International Symposium on the Properties of Water (ISOPOW) held in Bangkok, Thailand in 2007.